Joy, Learning, and Emotional Intelligence: Confucian Wisdom in Dialogue with the Bible and Contemporary Social Science - Hsiung, Ann-Marie (Philosophy and Realistic Reflection, 2026)
Confucian philosophy has shaped East Asia’s moral, social and educational life and still offers resources for human growth, yet its relevance is often underestimated. This article re-examines three interlocking themes—joy (le 樂 ), learning (xue 學 ), and self cultivation (xiushen 修 身 )—in conversation with the contemporary framework of emotional intelligence (EQ) in both educational and everyday contexts. Through close readings of the Analects, Mencius, the Doctrine of the Mean, and the Great Learning, this study sets classical insights alongside biblical passages that highlight joy, resilience, and relational harmony, as well as recent works in psychology and happiness studies. The comparison suggests that both Confucian and biblical traditions cultivate capacities now grouped under EQ— self-awareness, self-management, social awareness, and relationship management—while rooting them in purpose and community. Distinctive emphases emerge: Confucian texts stress attentional discipline and watchfulness (shendu 慎 獨 ); biblical writings emphasize prevailing joy that steadies people in adversity. Read with research on emotional intelligence, growth mindset, grit, and well-being, these sources broaden current understandings by embedding EQ within ethical and, for many, spiritual frameworks. The article argues that bringing ancient wisdom into dialogue with contemporary social science can enrich modern education, organizational leadership, and intercultural engagement, offering a more holistic and resilient vision of human flourishing in an increasingly fragmented world.